Pea (Pisum sativum L.) seed albumin extracts show anti‐inflammatory effect in the DSS model of mouse colitis. Issue 4 (2nd March 2015) - Utrilla, Mᵃ Pilar; Peinado, Mᵃ Jesus; Ruiz, Raquel; Rodriguez‐Nogales, Alba; Algieri, Francesca; Rodriguez‐Cabezas, Mᵃ Elena; Clemente, Alfonso; Galvez, Julio; Rubio, Luis A.
<x xml:space="preserve">Abstract</x> Scope This study investigates the preventive effects of two pea (Pisum sativum) seed albumin extracts, either in the presence (pea seed extract [PSE]) or absence (albumin fraction from PSE [AF‐PSE]) of soluble polysaccharides, in the dextran sodium sulfate (DSS) induced colitis in mice. Methods and results Male C57BL/6J mice were assigned to five groups: one noncolitic and four colitic. Colitis was induced by incorporating DSS (3.5%) in the drinking water for 4 days, after which DSS was removed. Treated groups received orally PSE (15 g/kg⋅day), or AF‐PSE (1.5 g/kg⋅day), or pure soy Bowman–Birk inhibitor (BBI; 50 mg/kg⋅day), starting 2 wk before colitis induction, and maintained for 9 days after. All treated groups showed intestinal anti‐inflammatory effect, evidenced by reduced microscopic histological damage in comparison with untreated colitic mice. The treatments ameliorated the colonic mRNA expression of different proinflammatory markers: cytokines, inducible enzymes, metalloproteinases, adhesion molecules, and toll‐like receptors, as well as proteins involved in maintaining the epithelial barrier function. Furthermore, the administration of PSE, AF‐PSE, or soy BBI restored bacterial counts, partially or totally, to values in healthy mice. Conclusion PSE and AF‐PSE ameliorated DSS‐induced damage to mice, their effects being due, at least partially, to the presence of active BBI.